Coming to Consensus on Policy to Create Supportive Built Environments and Community Design - Raine, Kim D. (Can J Public Health, 2012)
In April 2011, a conference with invited experts from research, policy and practice was held to build consensus around policy levers to address environmental determinants of obesity. The gap between existing policy tools and what can promote health through community design is a major policy opportunity. This commentary represents a consensus of next actions towards creating built environments that support healthy active living. The policy environment and Canadian evidence are reviewed. Issues and challenges to policy change are discussed. Recommendations to create supportive built environments that encourage healthy active living in communities include the following: 1) empower planning authorities to change bylaws that impede healthy active living, protect and increase access to green space, introduce zoning to increase high density, mixed land use, and influence the location and distribution of food stores; 2) establish stable funding for infrastructure promoting active transportation and opportunities for recreation; 3) evaluate the effectiveness of programs to improve the built environment so that successful interventions can be identified and disseminated; 4) mandate health impact assessment of planning, development and transportation policies to ensure that legislative changes promote health and safety; 5) frame issues to dispel myths and to promote protection from obesity risk factors.